Kajian tentang Pengaruh Brand Community Integration pada Loyalitas Merek Anggota IM3 @ School Community di SMAN 8 Malang - Primi Puspita Ramadhania; Nanang Suryadi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Objective of this research is to know and analize the effect of brand community integration to brand loyalty of IM3@scholl community members in SMAN 8 Malang, simultaneosly and partially and to know which variable plays the dominant role. The result of multiple regression analysis shows that simultaneosly, brand community integration variables( product, brand, company, other customers) affects brand loyalty variable in a positive and significant way. Partially, brand and other customer variables affect brand loyalty significantly, while product and company do not affect brand loyalty. The dominant variable in affecting brand loyalty is brand variable.Keywords: Brand Community Integration, brand loyalty, IM3 @ School Community.